Pengaruh Rebusan Akar Saluang Belum (Lavanga sarmentosa) Terhadap Jumlah Spermatid pada Gambaran Histologis Tubulus Seminiferus Mencit: Effectivity of Saluang Belum (Lavanga sarmentosa) on The Spermatids in Tubulus Seminiferus Histological of Mice - Silvani Permatasari; Hairunnida Rahmatina; Ratna Widayati; I Gde Eka A (Jurnal Surya Medika (JSM), 2023)
The Dayak tribe of Kalimantan is known as the root of Saluang Belum (Lavanga sarmentosa) a traditional medicinal plant that has properties to increase stamina, and sexual arousal and is used as an alternative medicine to increase male fertility. L.sarmentosa is consumed by drinking the boiled water of the plant's roots. The aim of this study is to determine the effect infusion roots of Saluang Belum (L.sarmentosa) in increasing the spermatids as seen in the tubulus seminiferus histological of mice (Mus musculus). The root will be extracted by the infusion method with different doses for each group, namely 200 mg/KgBB, 400 mg/KgBB, and 600 mg/KgBB, and negative controls (aquades) which was carried out for 15 days to mice. On the day 16, the right testis was taken and histological preparations were made with hematoxylin-eosin staining and observed under a microscope at 400x magnification in five fields of view. Compounds contained in the infusion of L.sarmentosa are alkaloids, saponins, triterpenoids, flavonoids, phenolics, and steroids. The number of spermatids in the tubulus seminiferus histological of mice increased statistically significantly from the doses of 200 mg/KgBB, 400 mg/KgBB, and 600 mg/KBBg. Conclusion: Infusion of the roots L.sarmentosa can increase the number of spermatids seen in the tubulus seminiferus histological of mice.